IMMU-42. OPTIMIZING IMMUNOTHERAPY FOR GLIOMA USING CYTOKINE-ACTIVATED NATURAL KILLER CELLS. (12th November 2021) - Kerstetter-Fogle, Amber; Otegbeye, Folashade; Soler, David; Harris, Peggy; Raghavan, Alankrita; Sloan, Andrew
Abstract: INTRODUCTION: Glioblastoma multiforme (GBM) is the most common primary central nervous system malignancy associated with a 12-15 month survival after surgery and radio-chemotherapy. Utilizing adoptive cellular immunotherapy using natural killer (NK) cells has developed over the past two decades for a variety of hematologic malignancies. This approach in solid malignancies is limited by questions of cell dose versus tumor burden, insufficient tumor infiltration, and a tumor microenvironment that suppresses NK cell function. METHODS: We isolated NK cells from healthy volunteers and activated them using IL-2, -15, -12, -18, then perform cytotoxic assays in the presence of glioma stem cells. We also tested the efficacy of the NK cells with intracranial delivery in a pre-clinical murine model of glioma. We tested various concentrations of IL-2 and IL-15 on the cytokine culture platform. RESULTS: In this study, we demonstrate human NK cells, activated using a cytokine cocktail of interleukins-2, -15, -12, and -18, exert strong cytotoxic events against glioma cell lines. To further examine the efficacy of activated NK cells in vitro, we utilized intracranially xenografted glioma lines and demonstrated a survival benefit with tumor bed injections of these cytokine-activated NK cells (p=0.0089). We were able to confirm that NK cells cultured with low doses (200u IL2; 50ng/ml IL15) of both cytokines are just as effective as higher doses. This is important, as in vivo exhaustion of NK cells stimulated with high doses of either cytokine has been well validated. We also found that low-dose irradiation (4Gy) of glioma cells prior to co-culture with cytokine-activated NK cells promoted increased targeted glioma cell killing within 4 hours(32% cell killing). CONCLUSIONS: These findings suggest that in a clinical study, injection of cytokine-activated NK cells into the glioblastoma tumor bed could be used as adjuvant treatment following either stereotactic radiation or surgical resection.